2010
DOI: 10.1111/j.1369-1600.2010.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural response of the appetitive emotional system in cocaine addiction: an fMRI Study

Abstract: Research on addiction suggests that emotional alterations play an essential role in the development, maintenance, relapse and treatment outcome of substance abuse disorders. Although many neuroimaging studies focussed on the neural response to conditioned stimuli, much less is known about the neural response to natural affective stimuli in this pathological population. Previous research has demonstrated an altered emotional experience and autonomic response to emotional stimuli using the International Affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 91 publications
6
70
1
Order By: Relevance
“…This was motivated by the knowledge that cocaine users appear to have a very low neural response to natural rewards (Cheetham et al, 2010), which typically engage the limbic system (eg the ventral MPFC, ACC, and striatum) (Asensio et al, 2010a;Kelley and Berridge, 2002). In addition, several resting state functional MRI studies have demonstrated lower baseline resting state functional connectivity with the MPFC in cocaine users Gu et al, 2007;Tomasi et al, 2010), though other studies have demonstrated that cocaine users have higher connectivity in these circuits (Camchong et al, 2011;Hu et al, 2015).…”
Section: Ventral Medial Prefrontal Cortex: Impaired Mobilization In Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This was motivated by the knowledge that cocaine users appear to have a very low neural response to natural rewards (Cheetham et al, 2010), which typically engage the limbic system (eg the ventral MPFC, ACC, and striatum) (Asensio et al, 2010a;Kelley and Berridge, 2002). In addition, several resting state functional MRI studies have demonstrated lower baseline resting state functional connectivity with the MPFC in cocaine users Gu et al, 2007;Tomasi et al, 2010), though other studies have demonstrated that cocaine users have higher connectivity in these circuits (Camchong et al, 2011;Hu et al, 2015).…”
Section: Ventral Medial Prefrontal Cortex: Impaired Mobilization In Cmentioning
confidence: 99%
“…The executive control loop includes projections from the dorsolateral prefrontal cortex (DLPFC) to the dorsal striatum. Cocaine users typically have an attenuated prefrontal cortex response to tasks that require mobilization of both the limbic circuit (eg natural rewards) (Asensio et al, 2010a;Cheetham et al, 2010;Kelley and Berridge, 2002). One of the only things which reliably activates the MPFC in this population appears to be drug cues (Childress et al, 2008;Goldstein et al, 2007;Hester and Garavan, 2009;Prisciandaro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a number of researchers have described [106,149], substance-use disorders are typically accompanied by decreased reward motivation for typical and non-pathological rewards, a phenomenon that has been variously termed ‘motivational toxicity’ [150] and ‘reward-deficiency syndrome’ [151]. For example, Asensio and collegues [152] reported hypoactivation of the dorsal and ventral striatum and the dorsomedial pre-frontal cortex when cocaine addicts viewed pleasant images not linked to substance cues. Gilman and Hommer [153] reported subjective hypoarousal to normative positive images in alcohol-dependent participants.…”
Section: Reviewmentioning
confidence: 99%
“…The prevailing view is that substance-related disorders represent an imbalance between the exaggerated value given to drugs (even after loss of originally strong rewarding effects) and the devalued appeal of a range of natural reinforcers, from food to sex or money (2). Various neuroimaging studies have demonstrated that cocainedependent users show increased activations in the main regions of the brain reward system (striatum, medial prefrontal cortex, and posterior cingulate cortex) in response to drug stimuli, coupled with significantly decreased activations in the same regions in response to sexual stimuli or monetary offers (3)(4)(5). Using an analogy, in the "addicted brain stock market," drug stocks would be continually overrated, and all competitors steadily underrated.…”
mentioning
confidence: 99%